Isaac Julien - what freedom is to me - Julien, Isaac 1960-; Nelson, Caleb Azumah 1993-; Balshaw, Maria 1970-; Bernier, Celeste-Marie 1975- (Tate Publishing, 2023)
Celebrated for his compelling lyrical films and video art installations, Isaac Julien is one of the leading artists working today. This landmark book reveals the scope of Julien's pioneering practice of over forty years, from the early 1980s to the present day, showcasing works from early films to large-scale, multi-screen installations which investigate the movement of peoples across different continents, times and spaces. It includes some of his early projects as part of Sankofa Film and Video Collective (1983-92); his critically acclaimed ten-screen film installation, Lessons of the Hour 2019, a portrait of the life and times of Frederick Douglass, the visionary African American orator, philosopher and self-liberated freedom-fighter; and Once Again (Statues Never Die) 2022. The wide range of writers and collaborators who have contributed to this book highlight Julien's critical thinking and the way his work breaks down barriers between different artistic disciplines, drawing from film, dance, photography, music, theatre, painting and sculpture by using the themes of desire, history and culture. Featuring strikingly beautiful reproductions of these extraordinarily powerful works, this publication enriches our understanding and appreciation of a remarkable artist
Rückseite Titelblatt: First published 2023 by order of the Tate Trustees by Tate Publishing (...) on the occasion of the exhibition "Isaac Julien: What Freedom Is To Me", Tate Britain, London, 26 April - 20 August 2023; Kunstsammlung Nordrhein-Westfalen, Düsseldorf, 23 September 2023 - 14 January 2024; Bonnefanten Museum, Maastricht, 4 February - 9 June 2024
Mit Augmented Reality App
Keywords: Julien, Isaac -- 1960-; Geschichte 1980-; Videokunst; Julien, Isaac / Criticism and interpretation; Julien, Isaac / (OCoLC)fst00299818; Video art; Video art / (OCoLC)fst01166389; Criticism, interpretation, etc / (OCoLC)fst01411635; Ausstellungskatalog -- Tate Britain -- 26.04.2023-20.08.2023 -- London; Ausstellungskatalog -- Stiftung Kunstsammlung Nordrhein-Westfalen -- 23.09.2023-14.01.2024 -- Düsseldorf; Ausstellungskatalog -- Bonnefanten Museum -- 04.02.2024-09.06.2024 -- Maastricht; Bildband